Chinese-English literacy translation as an economic network a freelance translator's experience-based perspective - Stenberg, Josh (Perspective in the Arts and Humanities ASIA (formerly Asian Perspectives in the Arts and Humanities), 2015)
This article examine Chinese-English literary translation as a field of professional endeavor within the last decade, drawing on the author's first-hand knowledge as a freelance translator and on secondary sources surrounding the processes of translator and on secondary sources surrounding the processes of translation and publication. Positing Chinese-English literary translation as the product of a global socioeconomic network, the essay examines, in succession, the questions "Who translate?" "Who funds?" "Who publishes" and "Who and what is being translated". The findings are that the field is presently experiencing growth, accompanied by a shift from the West towards Asia in term of funding, publication and geographic location of translators.